Effect of Tax Discrimination, Love of Money, and Possibility of Detecting Fraud on the Perceptions of Tax Evasion - Amanda Lathifah Putri Nabilah (RTTM, 2023)
Abstract This research aims to determine the effect of tax discrimination, love of money, and the possibility of detecting fraud on the perceptions of tax evasion. This research uses quantitative methods. The research data used is primary data with a research instrument in the form of a questionnaire. The population in this study were 4,211 MSME actors in the Central Jakarta area who were registered with the PPKUKM (Small and Medium Enterprise Cooperative Trading Industry) Agency. The sample in this study were 87 MSME actors. The data analysis method uses multiple linear analysis methods with the help of the SPSS version 22 program. According to the analysis's findings, tax discrimination positively affects perceptions of tax evasion, love of money negatively affects perceptions of tax evasion, and the possibility of detecting fraud does not affect perceptions of tax evasion. Keyword: Tax Discrimination; Love of Money; Possibility of Detecting Fraud; Perceptions; Tax Evasion